Spontaneous Ca2+ Fluctuations Arise in Thin Astrocytic Processes With Real 3D Geometry - Héja, László; Szabó, Zsolt; Péter, Márton; Kardos, Julianna (Frontiers in Cellular Neuroscience, 2021)
Fluctuations of cytosolic Ca2+ concentration in astrocytes are regarded as a critical non-neuronal signal to regulate neuronal functions. Although such fluctuations can be evoked by neuronal activity, rhythmic astrocytic Ca2+ oscillations may also spontaneously arise. Experimental studies hint that these spontaneous astrocytic Ca2+ oscillations may lie behind different kinds of emerging neuronal synchronized activities, like epileptogenic bursts or slow-wave rhythms. Despite the potential importance of spontaneous Ca2+ oscillations in astrocytes, the mechanism by which they develop is poorly understood. Using simple 3D synapse models and kinetic data of astrocytic Glu transporters (EAAT) and the Na+/Ca2+ exchanger (NCX), we have previously shown that NCX activity alone is able to generate markedly stable, spontaneous Ca2+ oscillation in the astrocytic leaflet microdomain. Here we extend that model by incorporating experimentally determined real 3D geometries of 208 excitatory synapses reconstructed from publicly available ultra-resolution electron microscopy datasets. Our simulations predict that the surface/volume ratio of peri-synaptic astrocytic processes prominently dictates whether NCX-mediated spontaneous Ca2+ oscillations emerge. We also show that increased levels of intracellular astrocytic Na+ concentration facilitates the appearance of Ca2+ fluctuations. These results further support the principal role of the dynamical reshaping of astrocyte processes in the generation of intrinsic Ca2+ oscillations and their spreading over larger astrocytic compartments.